Phase II clinical trial of phlebotomy for non‐alcoholic fatty liver disease. Issue 7 (26th February 2013) - Beaton, M. D.; Chakrabarti, S.; Levstik, M.; Speechley, M.; Marotta, P.; Adams, P.
Summary Background Elevated iron indices are described in non‐alcoholic fatty liver disease and iron reduction has been suggested as a potential therapy. Aim To determine whether phlebotomy is an effective therapy for non‐alcoholic fatty liver disease. Methods Patients with biopsy proven non‐alcoholic fatty liver disease underwent baseline evaluation to determine severity of metabolic and liver disease. A Phase II trial of phlebotomy was carried out to achieve near‐iron depletion (serum ferritin ≤50 μg/L or haemoglobin 100 g/L). Repeat liver biopsy, anthropometric and biochemical measurements were performed 6 months following the end of treatment. Primary outcome was improvement in liver histology, assessed using the non‐alcoholic fatty liver disease activity score. Results Thirty‐one patients completed follow‐up. Iron reduction resulted in a significant improvement in the non‐alcoholic fatty liver disease activity score (−0.74 ± 1.83, P = 0.019). Reductions in individual histological features of lobular inflammation (−0.29 ± 1.07, P = 0.182), steatosis (−0.26 ± 0.82, P = 0.134), hepatocyte ballooning (−0.19 ± 0.70, P = 0.213) did not achieve significance nor did the score for fibrosis (−0.32 ± 0.94, P = 0.099). Conclusions This prospective Phase II study of phlebotomy with paired liver biopsies evaluating phlebotomy therapy in non‐alcoholic fatty liver disease patients suggests that iron reduction may improve liver histology. However, the effect size of phlebotomy raises questions of whether treatment could have sufficient clinical significance to justify a definitive Phase III trial. This trial has been registered with the US National Institute of Health (clinicaltrials.gov, Identifier NCT 00641524).